2019
DOI: 10.4269/ajtmh.18-0806
|View full text |Cite
|
Sign up to set email alerts
|

Melioidosis in the Torres Strait Islands, Australia: Exquisite Interplay between Pathogen, Host, and Environment

Abstract: Burkholderia pseudomallei, a bacterium that lives in the soil of the tropics, causes the disease melioidosis. This retrospective study investigated the temporospatial epidemiology of the 49 laboratory-confirmed melioidosis cases in the Torres Straits Islands of tropical Australia between 1997 and 2017. An identifiable risk factor for the disease was present in 43/49 (88%) cases and in 35/36 (97%) cases with complete clinical data. The mean incidence of melioidosis varied across the region, from 0/100,000 perso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…B. pseudomallei is endemic to Far North Queensland (FNQ), a region in the northernmost part of the state of Queensland, Australia ( Figure 1 ). Incidence of melioidosis in the Torres Strait Islands in the region’s north is among the highest reported in published series of melioidosis cases in Australia ( 4 , 6 ). During the past 20 years, the FNQ population has grown rapidly, predominantly in the city of Cairns, the region’s major industrial hub, and in the nearby towns (Cairns area, in and around Cairns).…”
mentioning
confidence: 95%
“…B. pseudomallei is endemic to Far North Queensland (FNQ), a region in the northernmost part of the state of Queensland, Australia ( Figure 1 ). Incidence of melioidosis in the Torres Strait Islands in the region’s north is among the highest reported in published series of melioidosis cases in Australia ( 4 , 6 ). During the past 20 years, the FNQ population has grown rapidly, predominantly in the city of Cairns, the region’s major industrial hub, and in the nearby towns (Cairns area, in and around Cairns).…”
mentioning
confidence: 95%
“…Similar to the main findings of Chakravorty and Heath [29] and Hantrakun et al [30], the present work indicated that the provinces with hotspot clusters were primarily located in the northeast because their physical conditions and climate are agricultural land and drought. In particular, the melioidosis incidence is influenced by environmental factors, such as the rainfall, vegetation, soil type, humidity, temperature and climatic variations, that favor the growth of the causative organism [31][32][33]. On the contrary, with its sprawling urban areas around Bangkok and expanding industrial estates in many provinces, the central region was the main location for most coldspot clusters, indicating its low incidence rate of melioidosis induced by those factors [13].…”
Section: Discussionmentioning
confidence: 99%
“…4 In humans, melioidosis can involve almost any organ, with the clinical presentation a result of the complex interplay between host, pathogen, and the environment. 5,6 B. pseudomallei can also infect animals, with pigs, goats, sheep, and camels among the most susceptible. 4…”
Section: Introductionmentioning
confidence: 99%